Optimization of temperature rise during CO2 absorption process using response surface methodology - See, T.L. (Trans Tech Publications Ltd, 2014)
This study aims to optimize the temperature rise during CO2 absorption process using response surface methodology (RSM). Verification experiments were performed using a pilot scale experimental set up to validate the optimization condition generated from RSM analysis. The magnitude of temperature rise was observed to increase with increase of pressure and it was especially significant with the increase of CO2 inlet concentration. However, the increase of temperature with higher CO2 inlet concentration was not very obvious after 60 of CO2 inlet concentration. The predicted values of the optimized temperature rise were generally in good agreement with the actual experimental results and this indicated that the empirical correlation generated was well suited with the experimental results. Â© 2014 Trans Tech Publications, Switzerland.